Quantifying the environmental support to wild catch Alaskan sockeye salmon and farmed Norwegian Atlantic Salmon: An emergy approach. (1st October 2022) - Brown, Mark T.; Viglia, Silvio; Love, Dave; Asche, Frank; Nussbaumer, Elizabeth; Fry, Jillian; Hilborn, Ray; Neff, Roni
Abstract: Understanding the relative contributions of the environment to commercial fisheries and aquaculture systems is an area of intense importance as it quantifies the dependence these human dominated systems have on healthy and productive ecosystems. Measures of sustainability are required that include environmental support, use of nonrenewable resources, and labor & services. This work draws on primary and secondary data used in an emergy analysis approach to assess environmental support and sustainability of a wild catch sockeye salmon fishery in Bristol Bay, Alaska and Atlantic salmon aquaculture in Norway. The analyses ended at the processing gate for both production systems. Environmental support of the sockeye fishery amounted to 69% of total inputs for landed fish and 37% for processed fish, while the environmental support for farm raised Atlantic salmon was 60% and 42% for landed and processed fish respectively. Labor and services contributed 53% of total inputs for processed sockeye and 44% for Atlantic salmon. The emergy indices for the wild caught sockeye and farmed Atlantic salmon systems were relatively high having emergy yield ratios for landed fish of 3.2 (wild caught sockeye) and 2.3 (farmed Atlantic salmon). After processing emergy yields of both systems were 1.6 (sockeye) and 1.7 (Atlantic salmon). Environmental loading ratios for the sockeye fishery were 0.45 and 1.69 for landed salmon and processed fish respectively, while for Atlantic salmon they were 0.76 and 1.40 for harvested and processed fish respectively. Emergy sustainability indexes (ESI) for both production systems were much higher than other aquaculture systems. Landed sockeye salmon had an ESI of 7.2, while that of farmed raised Atlantic salmon was 3.0, somewhat lower, but still a relatively sustainable source of high-quality protein.